SwiftUI iOS13 Coffee Shop Application, Order Products Online - Kababyan, David (Packt Publishing, 2020)
Build a coffee shop application for iOS using Xcode 11, SwiftUI, iOS 13, Firebase Firestore, and Swift 5 About This Video Learn how to write clean and readable code Build a professional iOS application Explore SwiftUI In Detail In this course, you'll build a real online coffee ordering application using SwiftUI. This course is for iOS developers who know their way around Xcode and are familiar with Swift, SwiftUI, and application development. You'll learn how to build an application from the ground up alongside the instructor using all the assets provided. The course explains every line of code and shows you how to write clean and readable code and structure your app development in such a way that even if you get back to your code in a few years, you'll be able to read and understand it clearly. Even if you are an experienced iOS developer, you'll learn something new in this course.